2017
DOI: 10.1159/000472410
|View full text |Cite
|
Sign up to set email alerts
|

LincRNA-p21 Inhibits the Wnt/β-Catenin Pathway in Activated Hepatic Stellate Cells via Sponging MicroRNA-17-5p

Abstract: Background/Aims: It is known that the activation of hepatic stellate cells (HSCs) is a pivotal step in the initiation and progression of liver fibrosis. Aberrant activated Wnt/β-catenin pathway is known to accelerate the development of liver fibrosis. microRNAs (miRNAs)-mediated Wnt/β-catenin pathway has been reported to be involved in HSC activation during liver fibrosis. However, whether long noncoding RNAs (lncRNAs) regulate Wnt/β-catenin pathway during HSC activation still remains unclear. Methods: Long in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…Hepatic stellate cells (HSCs), the primary effector cells in the liver, are involved in the development of pathological fibrosis [23, 24]. Thus, insight into mechanisms that regulate HSC activation is considered key for the treatment of hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic stellate cells (HSCs), the primary effector cells in the liver, are involved in the development of pathological fibrosis [23, 24]. Thus, insight into mechanisms that regulate HSC activation is considered key for the treatment of hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Increasing studies suggested that lncRNAs played crucial roles in the initiation and development of tumor and deregulated expression of lncRNAs was found in several tumors. [27][28][29] Previous studies showed that lincRNA-p21 suppressed the hepatocellular carcinoma and colorectal cancer progression. [22][23][24][25][26] LincR-NA-p21 is a novel lncRNA, which was identified as one direct transcriptional target gene of p53.…”
Section: Introductionmentioning
confidence: 99%
“…lincRNA‐p21 enhanced PTEN expression by competitively binding to miR‐181b (Yu, Lu, Chen, Dong, & Zheng, ). Yu, Guo, et al () reported that lincRNA‐p21, a target of miR‐17‐5p, inhibits miR‐17‐5p level. Lack of the miR‐17‐5p binding site in lincRNA‐p21 prevented the inhibition of miR‐17‐5p expression.…”
Section: Dysregulation Of Lncrnas In Liver Fibrosismentioning
confidence: 99%
“…lincRNA-p21 enhanced PTEN expression by competitively binding to miR-181b (Yu, Lu, Chen, Dong, & Zheng, 2016). Yu, Guo, et al (2017) Knockdown of lncRNA-ATB could downregulate β-catenin expression by upregulating the endogenous miR-200a and suppress the activation of LX-2 cells. Yu, Zheng, Mao, Dong, Lu, Li, et al (2015) reported that GAS5 is downregulated in liver fibrosis and in activated HSCs, whereas GAS5 overexpression inhibits the activation of HSCs.…”
Section: The Interaction Of Lncrnas With Mirnasmentioning
confidence: 99%